Two new species of Bungona Harker, 1957 (Ephemeroptera: Baetidae) from Borneo, Indonesia - Marle, Pierre; Salles, Frederico F.; Gattolliat, Jean-Luc (Zootaxa, 2016)
Two new species of Bungona, belonging to the subgenera Chopralla Waltz & McCafferty, 1987 and Centroptella Braasch & Soldán, 1980, are described based on larvae from Kalimantan (Borneo, Indonesia). Bungona (Centroptella) papilionodes n. sp. is the third species described for the subgenus. It can be distinguished from Bungona (Centroptella) longisetosa (Braasch & Soldán, 1980) and Bungona (Centroptella) soldani (Müller-Liebenau, 1983) by the length of the maxillary palp, the presence or absence of an additional small denticle on the lateral margin of the distal incisor, and the spination of the paraproct. This new report of the subgenus greatly increases its geographic range of distribution, as it was known only from Sri-Lanka and China. Bungona (Chopralla) bintang n. sp. is the seventh species described for the subgenus Chopralla and the second described from Borneo. It differs from others species of the subgenus and especially from Bungona (Chopralla) pusilla (Müller-Liebenau, 1984) (Borneo) by the combination of lacking hindwing pads, the particular spination of distal margins of tergites, and the shape of the maxillary palp. The two new species fit into the recently revised concepts of Chopralla and Centroptella and confirm the characters used to support these taxa as valid subgenera.